Style Matters in Presocratic Philosophy, an Introduction - Vieira, Celso; Cornelli, Gabriele (Revista Archai, 2024)
What we envisaged as a dossier to explore the connection between style and philosophy in this unique transitional period of Presocratic philosophy has turned out to be a volume that breaks with several conventional views of the Presocratics and has the potential to take the interpretation of style and Presocratic philosophy in a whole new and more fruitful direction.